CIB2 interacts with TMC1 and TMC2 and is essential for mechanotransduction in auditory hair cells - Arnaud P. J. Giese (Nature Portfolio, 2017)
Inner ear hair cells detect sound through deflection of stereocilia that harbor mechanically-gated channels. Here the authors show that protein responsible for Usher syndrome, CIB2, interacts with these channels and is essential for their function and hearing in mice.